2022
DOI: 10.1101/2022.02.28.22271622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of diabetes mellitus on the stabilization and osseointegration of dental implants: a systematic review

Abstract: Introduction: Diabetes mellitus is a chronic metabolic disorder leading to hyperglycemia, which causes various complications due to vasculopathy. Adequate dental rehabilitation including dental implants plays a key role in promoting the eating habits of diabetics and better metabolic control. Aim: We performed a systematic literature review to investigate the effect of diabetes mellitus on the stabilization and osseointegration of dental implants. Methods: We searched PubMed and Scopus until October 2021. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The outcome of implant restoration is determined by osseointegration and peri‐implant bone preservation, both of which require the interplay of osteoblast proliferation, differentiation and maturation. This process could be affected by many local and systemic factors, with DM serving as one of the most significant influential elements (Chrcanovic et al, 2014; Katsiroumpa et al, 2022). A retrospective cohort study found that the highest risk of implant failure was due to DM among the causative factors, with an implant success rate of 68.75% and a failure risk 2.75 times higher than in healthy dental patients (Moy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of implant restoration is determined by osseointegration and peri‐implant bone preservation, both of which require the interplay of osteoblast proliferation, differentiation and maturation. This process could be affected by many local and systemic factors, with DM serving as one of the most significant influential elements (Chrcanovic et al, 2014; Katsiroumpa et al, 2022). A retrospective cohort study found that the highest risk of implant failure was due to DM among the causative factors, with an implant success rate of 68.75% and a failure risk 2.75 times higher than in healthy dental patients (Moy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of implant restoration is determined by osseointegration and peri-implant bone preservation, both of which require the interplay of osteoblast proliferation, differentiation and maturation. This process could be affected by many local and systemic factors, with DM serving as one of the most significant influential elements (Chrcanovic et al, 2014;Katsiroumpa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate dental rehabilitation with the use of implants is essential in promoting the eating habits of diabetic patients and better metabolic control (Chrcanovic et al, 2014). Several systematic reviews have investigated the effect of diabetes on the stabilization and osseointegration of dental implants resulting on mixed results (Andrade et al, 2021; Chen et al, 2013; Chrcanovic et al, 2014; Katsiroumpa et al, 2022; Oates et al, 2013; Shang & Gao, 2021). In general, when diabetes is under control, implant procedures are safe and diabetic patients seem to be able to achieve a survival rate of dental implants like that of non-diabetics.…”
Section: Introductionmentioning
confidence: 99%